Pengaruh Pemberian Pakan Formulasi terhadap Pertambahan Panjang Badan Anakan Burung Lovebird (Agapornis fischeri) Umur 15-60 Hari - Rose, Zita Xena Xaviera; Yanuartono, Yanuartono; Indarjulianto, Soedarmanto; Widyarini, Sitarina; Permana, Rief Ghulam Satriya (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Lovebirds (LB) are widely kept and bred as pets. The development of health and disease in chicks is the main problem faced by lovebird keepers, mainly because there is no special feed and feeding equipment for LBs. This research aims to study the development of body length increase in lovebird chicks fed formulated feed from the age of 15-60 days using a modified Handfeeding tool. This study used formulated feed and 30 clinically healthy 15-day-old LB calves. A total of 2 feed formulations were made using commercial chicken feed ingredients plus milk and rice. LB chicks were divided into three groups, ten birds each, consisting of group I, the formula I feed; group II, given formula II feed; and group III (control), given commercial bird feed. Lovebirds chicks are reared and fed by hand feeding from 15 to 60 days old and checked for body length development. The results of body length development between groups were analyzed descriptively. The average results of measuring the body length of lovebird chicks fed formula 1 were 5.64 cm at the age of 15 days to 9.58 cm at the age of 60 days, while formula 2 was 5.78 cm at the age of 15 days to 10.83 cm at the age of 60 days, and conventional feed is 5.79 cm at the age of 15 days to 12.45 cm at the age of 60 days. It was concluded that formulated feed provided less additional body for love bird chicks than commercial feed.Lovebird; Formulated bird feed